Composite material suitable for back plate glass of black photovoltaic module and preparation method and application of composite material
By using a double-layer structure of the bottom black glaze and the surface transparent polyurethane elastomer solution on the back panel glass of the black photovoltaic module, the problem of excessive attenuation of the photovoltaic reflectance ratio after high pressure cooking in the prior art is solved, and the photovoltaic reflectance ratio attenuation value is too large after high pressure cooking is achieved. High impact resistance and excellent aesthetics.
Patent Information
- Application Number
- CN202411369099.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-18
AI Technical Summary
After the high-pressure cooking test of the existing black photovoltaic module backplane glass, the photovoltaic reflectance ratio attenuation value of the glazed layer exceeds 2%, affecting its long-term outdoor fashion aesthetics.
A composite material including a base black glaze and a surface transparent polyurethane elastomer solution is used to form a double-layer structure of an enamel-plated layer and a transparent polyurethane elastomer layer. The black glaze on the bottom layer consists of water-soluble ink-adjusting oil, low-expanding glass powder and black pigment. The hard segment content of the transparent polyurethane elastomer solution on the surface is 30-35%.
While ensuring excellent adhesion, the impact resistance and high-pressure cooking resistance of the backplane glass are improved. The glaze layer has no layering, bubbles, cracking, powdering, or falling off. The photovoltaic reflectance attenuation value is ≤2%. Improves the long-term outdoor aesthetics of black photovoltaic modules.
Smart Images

Figure BDA0005069050540000071 
Figure BDA0005069050540000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic modules, and in particular to a composite material suitable for black photovoltaic module back glass, a preparation method of the composite material, and application of the composite material in black photovoltaic module back glass. Background Art
[0002] The black photovoltaic modules use black frames, black grid transparent back glass, and black busbars to enhance the "appearance" of details, conforming to the aesthetics of modern architecture, and are particularly suitable for black roofs and building facades of photovoltaic building integration (BIPV), which are fashionable and beautiful. Among them, the black grid is formed by glazing the adjacent cells on the surface of the photovoltaic module back glass.
[0003] The high pressure cooking (PCT) test is a rapid evaluation method for testing the weather resistance of glazed glass. The test conditions are specified in the T / CPIA0028.2-2021 "Glass for Photovoltaic Modules Part 2: Double-Glass Module Backplane Reflection Enhanced Coated Glass" standard: Both the glass sample and the laminate sample are placed in a test chamber, the test temperature is 121±0.5℃, the relative humidity is 99%-100%, and the test time is 48h. After the test, all samples are visually inspected to observe whether the glaze layer has stratification, bubbling, cracking, powdering, or falling off. The photovoltaic reflectance of the glass sample after aging is tested, and the photovoltaic reflectance attenuation value △R≤2% is calculated.
[0004] At present, the glaze layer of photovoltaic module backplane glass made of black glaze on the domestic market has excellent adhesion (≤1 level) with the photovoltaic module backplane glass, but when it is made into 2.0mm black photovoltaic module backplane glass, a 227g (38.1mm diameter) steel ball falls on the smooth surface (non-glazed surface) glaze strip at a height of only 0.4m and breaks. After the high pressure cooking (PCT) test, the photovoltaic reflectivity attenuation value of the glaze layer is △R>2%. These have greatly affected the long-term outdoor fashion aesthetics of the black glaze layer for photovoltaic modules. Summary of the invention
[0005] In order to overcome the defects of the prior art solutions, the purpose of the present invention is to provide a composite material suitable for black photovoltaic module back panel glass, including a bottom black glaze and a surface transparent polyurethane elastomer solution. At the same time, the present invention provides a black photovoltaic module back panel glass, which has a double-layer structure of a glaze layer formed by a bottom black glaze and a transparent polyurethane elastomer formed by a surface transparent polyurethane elastomer solution.
[0006] The present invention adopts the following technical solutions:
[0007] A composite material suitable for black photovoltaic module back plate glass comprises a bottom black glaze and a surface transparent polyurethane elastomer solution, wherein the raw material components of the bottom black glaze include water-soluble varnish, low expansion glass powder and black pigment, and the hard segment content of the surface transparent polyurethane elastomer solution is 30-35%.
[0008] The hard segment content is the percentage of the total mass of diisocyanate, chain extender and chain extender crosslinker in the surface transparent polyurethane elastomer to the total mass of oligomer diol, diisocyanate, chain extender and chain extender crosslinker, as shown in the above formula.
[0009] Hard segment content = (m 二异氰酸酯 +m 扩链剂 +m 扩链交联剂 ) / (m 低聚物二醇 +m 二异氰酸酯 +m 扩链剂 +m 扩链交联剂 )×100%.
[0010] The hard segment content of the transparent polyurethane elastomer solution is greater than 35%, and the impact resistance of the black photovoltaic module back glass made of it on the smooth surface (non-double-layer structure surface) of the glaze strip cannot reach a high impact resistance of 0.6m without breaking; the hard segment content of the transparent polyurethane elastomer solution is less than 30%, and the photovoltaic reflectivity attenuation value of the double-layer structure of the black photovoltaic module back glass after the high pressure cooking (PCT) test is △R>2%.
[0011] According to some preferred embodiments of the present invention, the raw material components of the bottom black glaze include 15-25 parts of water-soluble varnish, 45-55 parts of low-expansion glass powder and 25-35 parts of black pigment by weight. The low-expansion glass powder in the bottom black glaze can be melted and sintered at a tempering temperature of 600-720°C, and is used as a high-temperature adhesive to coat the black pigment and bond to the back panel glass of the photovoltaic module to obtain a glaze layer.
[0012] According to some preferred embodiments of the present invention, the softening temperature of the low expansion glass powder is 510-520°C, and the average linear expansion coefficient thereof at 50-300°C is (80-90)×10 -7 / K.
[0013] According to some preferred embodiments of the present invention, the black pigment is selected from one or both of copper oxide and copper chrome black.
[0014] According to some preferred embodiments of the present invention, the raw material components of the surface transparent polyurethane elastomer solution include, by weight, 30-40 parts of oligomer diol, 10-20 parts of diisocyanate, 0.1-0.5 parts of catalyst, 1-3 parts of chain extender, 1-3 parts of chain extender crosslinker, 90-100 parts of solvent, and 0.4-1 parts of auxiliary agent. The catalyst is an organic tin catalyst. The auxiliary agent is a leveling agent and a defoamer, wherein the leveling agent is 0.2-0.5 parts, and the defoamer is 0.2-0.5 parts.
[0015] According to some preferred embodiments of the present invention, the oligomer diol may be selected from one or two of polycaprolactone diol and polycarbonate diol, the diisocyanate may be selected from one or more of isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), and 4,4′-dicyclohexylmethane diisocyanate (HMDI), the organotin catalyst may be selected from Air Chemical T-12, the chain extender may be selected from one or more of ethylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol, the chain extender crosslinker may be selected from one or two of trimethylolpropane and propylene glycol, the solvent may be selected from one or more of dimethyl carbonate, butyl acetate, and dimethylformamide, the leveling agent may be selected from Evonik TEGO Glide 450, and the defoamer may be selected from EFKA-2020.
[0016] According to some preferred embodiments of the present invention, the raw material components of the water-soluble varnish include, by weight: 35-50 parts of tripropylene glycol methyl ether, 15-30 parts of diethylene glycol butyl ether, 20-40 parts of water-soluble acrylic resin, 1-5 parts of ethyl cellulose and 1-5 parts of aqueous dispersant.
[0017] The present invention also provides a method for preparing the composite material as described above, comprising the following steps:
[0018] The water-soluble varnish, low expansion glass powder and black pigment are mixed and dispersed evenly, ground to a fineness value of less than 20 μm, and filtered to obtain a bottom black glaze;
[0019] Mix and stir the oligomer diol, diisocyanate and catalyst, heat to 80-90°C, keep warm and react for 3-4 hours; keep stirring, cool to 50-60°C, add chain extender, chain extender cross-linking agent and solvent, heat to 80-90°C, keep warm and react for 3-4 hours; cool to room temperature, add additives, mix well to obtain a surface transparent polyurethane elastomer solution.
[0020] According to some preferred embodiments of the present invention, the water-soluble varnish is prepared by the following method: tripropylene glycol methyl ether, diethylene glycol butyl ether, water-soluble acrylic resin and ethyl cellulose are mixed and heated, dissolved by heat preservation, an aqueous dispersant is added, mixed and dispersed until uniform, and cooled to room temperature to obtain a water-soluble varnish.
[0021] The present invention also provides a black photovoltaic module back panel glass, which has a glaze layer and a transparent polyurethane elastomer layer coated on the glaze layer, wherein the glaze layer is formed by the bottom black glaze in the composite material as described above, and the transparent polyurethane elastomer layer is formed by the surface transparent polyurethane elastomer solution in the composite material as described above.
[0022] According to some preferred implementation aspects of the present invention, the dry film thickness of the glaze layer is 10-20 μm, and the dry film thickness of the transparent polyurethane elastomer layer is 20-30 μm.
[0023] The present invention also provides a method for preparing the black photovoltaic module back panel glass as described above, wherein a bottom layer of black glaze is coated on the surface of the photovoltaic module back panel glass at the gaps between adjacent battery cells, and a glaze layer is formed through curing and tempering treatment, and a surface transparent polyurethane elastomer solution is sprayed on the surface of the glaze layer, and a transparent polyurethane elastomer layer is formed through curing treatment, thereby obtaining the black photovoltaic module back panel glass.
[0024] The present invention also provides a photovoltaic module, comprising a front glass panel, a front packaging material layer, a battery layer, a rear packaging material layer, and a back glass panel arranged in sequence from top to bottom, wherein the back glass panel is the black photovoltaic module back glass panel as described above.
[0025] Due to the adoption of the above technical scheme, the present invention has the following advantages over the prior art: the composite material suitable for the back plate glass of a black photovoltaic module of the present invention comprises a bottom black glaze and a surface transparent polyurethane elastomer solution, and is applied to the back plate glass of a black photovoltaic module, so that the back plate glass has a double-layer structure of a glaze layer formed by the bottom black glaze and a transparent polyurethane elastomer layer formed by the surface transparent polyurethane elastomer solution. The double-layer structure is made into a 2.0 mm black photovoltaic module back plate glass under the premise of ensuring excellent adhesion (≤1 level), and a 227 g (38.1 mm in diameter) steel ball falls on the smooth surface (non-double-layer structure surface) at a height of 0.6 m without breaking, and after a high pressure cooking (PCT) test, the glaze layer in the double-layer structure has no delamination, blistering, cracking, powdering, or falling off, and the photovoltaic reflectance attenuation value △R of the double-layer structure is ≤2%. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0027] The black photovoltaic module of this embodiment includes a front plate glass, a front encapsulation material layer, a battery layer, a rear encapsulation material layer, and a back plate glass arranged in sequence from top to bottom, and the back plate glass is a black photovoltaic module back plate glass. The black photovoltaic module back plate glass has a glaze layer and a transparent polyurethane elastomer layer coated on the glaze layer, the glaze layer is formed by the bottom black glaze in the composite material, and the transparent polyurethane elastomer layer is formed by the surface transparent polyurethane elastomer solution in the composite material. The dry film thickness of the glaze layer is 10-20 μm, and the dry film thickness of the transparent polyurethane elastomer layer is 20-30 μm.
[0028] The preparation method of the black photovoltaic module back panel glass of the present embodiment is as follows: a bottom layer of black glaze is applied on the surface of the photovoltaic module back panel glass at the gaps between adjacent battery cells, and a glaze layer is formed after being cured (180-200°C), tempered (600-720°C), and cooled; a surface layer of transparent polyurethane elastomer solution is then sprayed on the surface of the glaze layer, and a transparent polyurethane elastomer layer is formed after being cured (140-160°C) by medium-temperature baking and cooling, thereby obtaining a black photovoltaic module back panel glass having a double-layer structure of a glaze layer and a transparent polyurethane elastomer layer.
[0029] The double-layer structure is made into 2.0mm photovoltaic black module back panel glass while ensuring excellent adhesion (≤level 1). A 227g (diameter 38.1mm) steel ball drops on the smooth surface (non-double-layer structure surface) at a height of 0.6m without breaking, and has high impact resistance. After the high pressure cooking (PCT) test, the glaze layer in the double-layer structure has no delamination, blistering, cracking, powdering, or falling off, and the photovoltaic reflectance attenuation value △R of the double-layer structure is ≤2%.
[0030] The composite material suitable for the back glass of the black photovoltaic module in this embodiment includes a bottom black glaze and a surface transparent polyurethane elastomer solution. The raw material components of the bottom black glaze include water-soluble varnish, low-expansion glass powder and black pigment.
[0031] The raw material components of the bottom black glaze include 15-25 parts of water-soluble varnish, 45-55 parts of low-expansion glass powder and 25-35 parts of black pigment by weight.
[0032] The softening temperature of low expansion glass powder is 510-520℃, and its average linear expansion coefficient at 50-300℃ is (80-90)×10 -7 / K. The low expansion glass powder in the bottom black glaze can be melted and sintered at a tempering temperature of 600-720°C, and is used as a high temperature adhesive to coat the black pigment and bond to the back panel glass of the photovoltaic module to obtain a glaze layer.
[0033] Wherein, the black pigment is selected from one or both of copper oxide and copper chrome black.
[0034] The raw material components of the surface transparent polyurethane elastomer solution include, by weight, 30-40 parts of oligomer diol, 10-20 parts of diisocyanate, 0.1-0.5 parts of organic tin catalyst, 1-3 parts of chain extender, 1-3 parts of chain extender crosslinker, 90-100 parts of solvent, 0.2-0.5 parts of leveling agent and 0.2-0.5 parts of defoamer. The hard segment content in the transparent polyurethane elastomer solution is 30-35%.
[0035] Among them, hard segment content = (m 二异氰酸酯 +m 扩链剂 +m 扩链交联剂 ) / (m 低聚物二醇 +m 二异氰酸酯 +m 扩链剂 +m 扩链交联剂 )×100%.
[0036] Among them, the oligomer diol can be selected from one or two of polycaprolactone diol and polycarbonate diol, the diisocyanate can be selected from one or more of isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), and 4,4′-dicyclohexylmethane diisocyanate (HMDI), the organic tin catalyst can be selected from Air Chemical T-12, the chain extender can be selected from one or more of ethylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol, the chain extender cross-linking agent can be selected from one or two of trimethylolpropane and propylene glycol, the solvent can be selected from one or more of dimethyl carbonate, butyl acetate, and dimethylformamide, the leveling agent can be selected from Evonik TEGO Glide 450, and the defoaming agent can be selected from EFKA-2020.
[0037] The raw material components of the water-soluble varnish include, by weight: 35-50 parts of tripropylene glycol methyl ether, 15-30 parts of diethylene glycol butyl ether, 20-40 parts of water-soluble acrylic resin, 1-5 parts of ethyl cellulose and 1-5 parts of aqueous dispersant.
[0038] The method for preparing the composite material suitable for the back glass of the black photovoltaic module in this embodiment comprises the following steps:
[0039] 1) Preparation of water-soluble varnish
[0040] In parts by weight, 35-50 parts of tripropylene glycol methyl ether, 15-30 parts of diethylene glycol butyl ether, 20-40 parts of water-soluble acrylic resin and 1-5 parts of ethyl cellulose are mixed, stirred and heated to 50-60°C, and kept warm for 2-4 hours to dissolve, 1-5 parts of aqueous dispersant are added, mixed and dispersed until uniform, and cooled to room temperature to obtain water-soluble varnish.
[0041] 2) Preparation of bottom black glaze
[0042] By weight, 15-25 parts of water-soluble varnish, 45-55 parts of low-expansion glass powder and 25-35 parts of black pigment are mixed and dispersed uniformly, ground to a fineness of less than 20 μm by a three-roll grinder, and filtered by vibration to obtain a bottom black glaze.
[0043] 3) Preparation of surface transparent polyurethane elastomer solution
[0044] In parts by weight, 30-40 parts of oligomer diol, 10-20 parts of diisocyanate and 0.1-0.5 parts of organic tin catalyst are added to a reaction kettle, and under the protection of nitrogen replacement, the mixture is stirred and heated to 80-90°C for insulation and reaction for 3-4 hours; while maintaining stirring, the mixture is cooled to 50-60°C, 1-3 parts of chain extender, 1-3 parts of chain extender crosslinker and 90-100 parts of solvent are added, the mixture is heated to 80-90°C for insulation and reaction for 3-4 hours; the mixture is cooled to room temperature, 0.2-0.5 parts of leveling agent and 0.2-0.5 parts of defoaming agent are added, and the mixture is stirred for 15-20 minutes until uniform, so as to obtain a surface transparent polyurethane elastomer solution.
[0045] Example 1
[0046] The preparation of the composite material suitable for the back glass of the black photovoltaic module in this embodiment includes the following steps:
[0047] 1) Preparation of water-soluble varnish
[0048] In parts by weight, 40 parts of tripropylene glycol methyl ether, 25 parts of diethylene glycol butyl ether, 30 parts of water-soluble acrylic resin and 3 parts of ethyl cellulose are mixed, stirred and heated to 60°C, and kept warm for 2 hours to dissolve, 2 parts of aqueous dispersant are added, mixed and dispersed until uniform, and cooled to room temperature to obtain water-soluble varnish.
[0049] 2) Preparation of bottom black glaze
[0050] By weight, 25 parts of water-soluble varnish, 50 parts of low-expansion glass powder and 25 parts of copper oxide are mixed and dispersed uniformly, ground to a fineness of less than 20 μm by a three-roll grinder, and filtered by vibration to obtain a bottom black glaze.
[0051] The softening temperature of the low expansion glass powder in this embodiment is 510°C, and its average linear expansion coefficient at 50-300°C is 82×10 -7 / K.
[0052] 3) Preparation of surface transparent polyurethane elastomer solution
[0053] In parts by weight, 35 parts of polycaprolactone diol (number average molecular weight Mn=2000), 12 parts of 4,4′-dicyclohexylmethane diisocyanate (HMDI), and 0.3 parts of T-12 were added to a reactor, and under the protection of nitrogen replacement, the mixture was stirred and heated to 90°C for insulation and reaction for 3 hours; while maintaining stirring, the mixture was cooled to 60°C, 2 parts of 1,4-butanediol, 1 part of trimethylolpropane, and 100 parts of dimethylformamide were added, the mixture was heated to 90°C for insulation and reaction for 3 hours; the mixture was cooled to room temperature, 0.3 parts of TEGO Glide 4500 and 0.3 parts of EFKA-2020 were added, and the mixture was stirred for 20 minutes until uniform, thereby obtaining a surface transparent polyurethane elastomer solution.
[0054] The hard segment content of the transparent polyurethane elastomer solution in this embodiment is 30%.
[0055] Example 2
[0056] The difference between Example 2 and Example 1 is that the softening temperature of the low expansion glass powder in the bottom black glaze is 520°C, and its average linear expansion coefficient at 50-300°C is 87×10 -7 / K.
[0057] Example 3
[0058] The only difference between Example 3 and Example 1 is that the raw material component 4,4′-dicyclohexylmethane diisocyanate (HMDI) in the surface transparent polyurethane elastomer solution is 14 parts, and the hard segment content of the transparent polyurethane elastomer solution in this example is 33%.
[0059] Comparative Example 1
[0060] The difference between Comparative Example 1 and Example 1 is that the softening temperature of the low expansion glass powder in the bottom black glaze is 510°C, and its average linear expansion coefficient at 50-300°C is 95×10 -7 / K.
[0061] Comparative Example 2
[0062] The difference between Comparative Example 2 and Example 1 is that the raw material component polycaprolactone diol (number average molecular weight Mn=2000) in the surface transparent polyurethane elastomer solution is 25 parts, and the hard segment content of the transparent polyurethane elastomer solution in this example is 38%.
[0063] Comparative Example 3
[0064] The difference between Comparative Example 3 and Example 1 is that the raw material component polycaprolactone diol (number average molecular weight Mn=2000) in the surface transparent polyurethane elastomer solution is 36 parts, and the hard segment content of the transparent polyurethane elastomer solution in this example is 29%.
[0065] The composite materials in Examples 1-3 and Comparative Examples 1-3 are made into black photovoltaic module backplane glass, and the preparation method is as follows: a bottom layer of black glaze is silk-screened on the light-transmitting part of the photovoltaic module backplane glass surface where the cells are connected, and a glaze layer is formed after a curing treatment at 200°C, a tempering treatment at 720°C, and a cooling treatment; then a surface transparent polyurethane elastomer solution is sprayed on the surface of the glaze layer, and a medium-temperature baking curing treatment at 150°C and a cooling treatment are performed to form a transparent polyurethane elastomer layer, and a black photovoltaic module backplane glass with a double-layer structure of a glaze layer and a transparent polyurethane elastomer layer is obtained.
[0066] The performance of the black photovoltaic module back glass produced in Examples 1-3 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1 below:
[0067] Table 1 Test results
[0068]
[0069]
[0070] Table 1 related performance tests were conducted using the following methods:
[0071] Adhesion: Tested according to T / CPIA 0028.2-2021;
[0072] Impact resistance of smooth surface (non-double-layer structure surface): 2.0mm black photovoltaic module back panel glass is placed horizontally, and a 227g (diameter 38.1mm) steel ball falls on the glaze strip on its smooth surface (non-double-layer structure surface), and the maximum height value without breaking;
[0073] High Pressure Cooking (PCT) Test: Tested in accordance with T / CPIA 0028.2-2021.
[0074] The results in Table 1 show that the double-layer structure of the black photovoltaic module back panel glass made by Examples 1-3 of the present invention has excellent adhesion to the photovoltaic module back panel glass; the impact resistance height of the glaze strip on its smooth surface (non-double-layer structure surface) reaches 0.6m; after the high pressure cooking (PCT) test, the glaze layer in the double-layer structure has no delamination, blistering, cracking, powdering, and falling off, and the photovoltaic reflectance attenuation value △R of the double-layer structure is ≤2%.
[0075] The black photovoltaic module back panel glass made in Comparative Example 1 has an impact resistance height of only 0.4m at the glaze strip on the smooth surface (non-double-layer structure surface); the black photovoltaic module back panel glass made in Comparative Example 2 has an impact resistance height of 0.5m at the glaze strip on the smooth surface (non-double-layer structure surface); after the high pressure cooking (PCT) test of the black photovoltaic module back panel glass made in Comparative Example 3, the photovoltaic reflectance attenuation value △R of the double-layer structure is greater than 2%.
[0076] The composite material suitable for the back plate glass of a black photovoltaic module of the present invention comprises a bottom black glaze and a surface transparent polyurethane elastomer solution, and is applied to the back plate glass of the black photovoltaic module, so that the back plate glass has a double-layer structure of a glaze layer formed by the bottom black glaze and a transparent polyurethane elastomer layer formed by the surface transparent polyurethane elastomer solution. The double-layer structure is made into a 2.0mm black photovoltaic module back plate glass under the premise of ensuring excellent adhesion (≤1 level), and a 227g (38.1mm in diameter) steel ball falls on the smooth surface (non-double-layer structure surface) glaze strip at a height of 0.6m without breaking, and after a high pressure cooking (PCT) test, the glaze layer in the double-layer structure has no delamination, bubbling, cracking, powdering, and falling off, and the photovoltaic reflectance attenuation value △R of the double-layer structure is ≤2%. Therefore, the double-layer structure can effectively improve the long-term outdoor fashion and aesthetics of the black photovoltaic module.
[0077] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite material suitable for black photovoltaic module back glass, characterized in that: The invention comprises a bottom black glaze and a surface transparent polyurethane elastomer solution. The raw material components of the bottom black glaze include water-soluble varnish oil, low expansion glass powder and black pigment. The hard segment content of the surface transparent polyurethane elastomer solution is 30-35%.
2. The composite material according to claim 1, characterized in that By weight, the raw material components of the bottom black glaze include 15-25 parts of water-soluble varnish, 45-55 parts of low-expansion glass powder and 25-35 parts of black pigment.
3. The composite material according to claim 1, characterized in that The softening temperature of the low expansion glass powder is 510-520°C, and the average linear expansion coefficient thereof at 50-300°C is (80-90)×10 -7 / K.
4. The composite material according to claim 1, characterized in that By weight, the raw material components of the surface transparent polyurethane elastomer solution include 30-40 parts of oligomer diol, 10-20 parts of diisocyanate, 0.1-0.5 parts of catalyst, 1-3 parts of chain extender, 1-3 parts of chain extender crosslinker, 90-100 parts of solvent and 0.4-1 parts of auxiliary agent.
5. A method for preparing a composite material according to any one of claims 1 to 4, characterized in that: The steps include: The water-soluble varnish, low expansion glass powder and black pigment are mixed and dispersed evenly, ground to a fineness value of less than 20 μm, and filtered to obtain a bottom black glaze; Mix and stir the oligomer diol, diisocyanate and catalyst, heat to 80-90°C, keep warm and react for 3-4 hours; keep stirring, cool to 50-60°C, add chain extender, chain extender cross-linking agent and solvent, heat to 80-90°C, keep warm and react for 3-4 hours; cool to room temperature, add additives, mix well to obtain a surface transparent polyurethane elastomer solution.
6. The preparation method according to claim 5, characterized in that: The water-soluble varnish is prepared by the following method: tripropylene glycol methyl ether, diethylene glycol butyl ether, water-soluble acrylic resin and ethyl cellulose are mixed and heated, dissolved by heat preservation, an aqueous dispersant is added, mixed and dispersed until uniform, and cooled to room temperature to obtain the water-soluble varnish.
7. A black photovoltaic module back panel glass, characterized in that: The black photovoltaic module back panel glass has a glaze layer and a transparent polyurethane elastomer layer coated on the glaze layer, the glaze layer is formed by the bottom black glaze in the composite material as described in any one of claims 1-4, and the transparent polyurethane elastomer layer is formed by the surface transparent polyurethane elastomer solution in the composite material as described in any one of claims 1-4.
8. The black photovoltaic module back panel glass according to claim 7, characterized in that: The dry film thickness of the glaze layer is 10-20 μm, and the dry film thickness of the transparent polyurethane elastomer layer is 20-30 μm.
9. A method for preparing a black photovoltaic module back plate glass according to claim 7 or 8, characterized in that: A bottom layer of black glaze is applied on the surface of the photovoltaic module back panel glass at the gaps between adjacent cells, and a glaze layer is formed through curing and tempering. A surface transparent polyurethane elastomer solution is sprayed on the surface of the glaze layer, and a transparent polyurethane elastomer layer is formed through curing to obtain the black photovoltaic module back panel glass.
10. A photovoltaic module, comprising a front glass plate, a front encapsulation material layer, a battery layer, a rear encapsulation material layer, and a back glass plate arranged in order from top to bottom, characterized in that: The back panel glass is the black photovoltaic module back panel glass as described in claim 7 or 8.
Citation Information
Patent Citations
Full-black photovoltaic module
CN111430488A
Impact-resistant glass cover plate, preparation method thereof and electronic equipment
CN112358195A
Degradable electroactive polyurethane material as well as preparation method and application thereof
CN112940218A
Composite material suitable for photovoltaic glass as well as preparation method and application of composite material
CN115010382A
Basecoat-clearcoat film
US5268215A